1996
DOI: 10.1007/bf01499352
|View full text |Cite
|
Sign up to set email alerts
|

Life under Wainwright v. Witt: Juror dispositions and death qualification.

Abstract: The current standard for determining juror qualification in cases in which the prosecution is seeking the death penalty was formulated by the U.S. Supreme Court in 1985 in Wainwright v. Witt. This standard differs importantly from its predecessor, and requires that prospective jurors be dismissed if their views would prevent or substantially impair their ability to perform their functions as jurors. We assessed respondents according to the criteria imposed by Witt. We also measured independently prospective ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…Their stimulus materials were replicated and randomly assigned to subsequent participants. This method of screening for death qualification was based on the current standard for death qualification in Wainwright v. Witt (1985) and was adapted from research by Dillehay and Sandys (1996). Although it is likely that more individuals would be excluded from capital juries following an actual voir dire, those eliminated solely because they are not death qualified would be subject to the same standard used in the present study.…”
Section: Study 1: Methodsmentioning
confidence: 99%
“…Their stimulus materials were replicated and randomly assigned to subsequent participants. This method of screening for death qualification was based on the current standard for death qualification in Wainwright v. Witt (1985) and was adapted from research by Dillehay and Sandys (1996). Although it is likely that more individuals would be excluded from capital juries following an actual voir dire, those eliminated solely because they are not death qualified would be subject to the same standard used in the present study.…”
Section: Study 1: Methodsmentioning
confidence: 99%
“…In fact, research has suggested that the adoption of the Witt standard has had significant consequences. For example, Dillehay and Sandys (1996) found that 28% of participants who met the Witt standard would, contrary to law, automatically impose the death penalty. In fact, 36% of all venirepersons exhibited attitudes toward the death penalty that were so vehement that it prevented them from being impartial in a capital case.…”
Section: First Marketingmentioning
confidence: 95%
“…Death-sentencing procedures in the five "judge-sentencing" states and in the four "advisory" states must, at a minimum, require juries to decide all facts necessary to support a sentence of death to be in conformance with Ring. 20 Researchers estimate that the death and life qualification of capital juries may exclude anywhere between 11% and 40% of otherwise eligible jurors (Acker et al, 1999, p. 55;Dillehay & Sandys, 1996;Haney et al, 1994, p. 627;Thompson, 1989, p. 209). 21 A relatively small number of potential jurors are "nullifiers"; that is, their views about the death penalty are so strong that they cannot render a fair verdict on guilt or innocence.…”
Section: Jury Selection and Other Issues Involving The Capital Jurymentioning
confidence: 99%
“…Similarly, prospective jurors whose adamant approval of the death penalty would compromise their ability to consider imposing a sentence other than death are not qualified to serve in capital trials (Morgan v. Illinois, 1992). The impact of this latter process, known as "life qualification" or "reverse Witherspooning," on the composition and function of capital juries is not as well understood as the consequences of death-qualifying jurors (Acker, Brody, Harmon, & Richeson, 1999;Dillehay & Sandys, 1996;Haney, Hurtado, & Vega, 1994). The death qualification process threatens both the impartiality and representativeness of guilt-phase juries (Sandys & McClelland, 2003).…”
Section: Jury Selection and Other Issues Involving The Capital Jurymentioning
confidence: 99%